Coronary artery abnormalities in pediatric patients: classification. - José Jesús García Mendiola (Medisur)
Coronary artery anomaly is defined as any anatomical pattern that is apart from the normal element in regard to their origin, number, distribution and course. Through different mechanisms, it could be the cause of t thoracic pain, sudden death, myocardiopathy, syncope, myocardial infarction and ventricular fibrillation. These constitute a group of malformations which can be classified into, congenital, acquired and associated to other cardiac entities malformations. Due to the importance of this topic for cardiologists and specifically to pediatric cardiologists, this bibliographical revision about abnormalities classification is carried out.